1998
DOI: 10.1142/s0192415x98000397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Garlic Compounds Diallyl Sulfide and Diallyl Disulfide on Arylamine N-Acetyltransferase Activity in Strains ofHelicobacter pylorifrom Peptic Ulcer Patients

Abstract: Arylamine N-acctyltransferase (NAT) activities with p-aminobenzoic acid (PABA) and 2-aminofluorene (2-AF) were determined in the bacterium Helicobacter pylori collected from peptic ulcer patients. Two assay systems were performed, one with cellular cytosols, the other with intact cell suspensions. Cytosols or suspensions of H. pylori with or without specific concentrations of diallyl sulfide (DAS) or diallyl disulfide (DADS) co-treatment showed different percentages of 2-AF and PABA acetylation. The data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The bactericidal activity of these sulfides correlates with the number of sulfur atoms contained within them (73). It has also been indicated that the bactericidal effects of DAS and DADS on H. pylori, K. pneumoniae, and P. aeruginosa were due to their activity with respect to inhibition of arylamine N-acetyltransferase, an enzyme found in these pathogens (18,19,37,53,73). In another study, a 30-min exposure of C. albicans to DADS (0.5 mM) induced 70% cell death within 2 h. The early intracellular events associated with DADS-induced cell death corresponded to increased oxidative stress mediated through decreased GSH levels, resulting in the drastic death of C. albicans organisms (51).…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal activity of these sulfides correlates with the number of sulfur atoms contained within them (73). It has also been indicated that the bactericidal effects of DAS and DADS on H. pylori, K. pneumoniae, and P. aeruginosa were due to their activity with respect to inhibition of arylamine N-acetyltransferase, an enzyme found in these pathogens (18,19,37,53,73). In another study, a 30-min exposure of C. albicans to DADS (0.5 mM) induced 70% cell death within 2 h. The early intracellular events associated with DADS-induced cell death corresponded to increased oxidative stress mediated through decreased GSH levels, resulting in the drastic death of C. albicans organisms (51).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Chung et al (1998) inhibit both susceptible and drug-resistant H. pylori. Previous studies reported that DADS, DAT and PA could effectively inhibit the growth of several pathogens responsible for nosocomial infection including MRSA, Klebsiella pneumoniae and Pseudomonas aeruginosa (Tsao and Yin, 2001;Tsao et al, 2003;Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro and in vivo inhibitory activities of these sulphides against nosocomial pathogens such as methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae, Pseudomonas aeruginosa have been studied in our laboratory (Tsao and Yin, 2001;Tsao et al, 2003). It has been reported that DADS and/or DAT could inhibit the growth of susceptible H. pylori (Chung et al, 1998;O'Gara et al, 2000). However, it remains unknown whether these agents could inhibit drug resistant H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Diallyl sulfide (DAS), one of the component of garlic, has been reported to act as a potential chemopreventive function for many human cancer such as colon, lung, and skin (24). In our earlier studies, DAS inhibited the N-acetyltransferase activity in bacteria (25,26), human colon cancer cells (27) and bladder cancer cells (28), and inhibits murine WEHI-3 leukemia cells in BALB/c mice in vitro and in vivo (29). However, the mechanistic role of DAS-mediated apoptosis in human cervical cancer cells, especially the role of ER stress, caspases, and mitochondria in the induction of apoptosis remains limited.…”
Section: Introductionmentioning
confidence: 95%